DESAIN PEMBELAJARAN METODE NUMBERED HEAD TOGETHER (NHT) DENGAN MEDIA PETA BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR PADA SEMESTER GENAP 2019/2020 - Faridatus Sholihah; Nanik Ulfa (WANIAMBEY : Jurnal Pendidikan Dasar Islam, 2020)
This research is motivated by the low cognitive learning outcomes of students in the thematic learning of Class IV Indonesian Cultural Diversity. The contributing factor is the lack of variation in the learning methods and media used. This results in low student knowledge, especially on cultural diversity. To solve this problem, the researchers applied the Numbered Head Together (NHT) method with the Cultural Map Media so that student learning outcomes could improve. This study uses the PTK model from Kemmis and Mc Taggart which consists of 4 stages including: planning (planning), action (action), observation (observing) and reflection (reflection). However, given the increasing spread of Covid-19, the research was stopped until the planning stage provided that all research instruments had to be validated. The results of the instrument validation were: RPP percentage score was 78.5%; percentage score of learning media 86%; Group worksheet score 82.5%; score percentage of written test questions 84.5%; the observation guideline percentage score was 78%. Based on the results of instrument validation, it can be concluded that all instruments obtain valid criteria and are suitable for use in the learning process.